The Gendered Construction of Science - Block, Amy (UnderCurrents: Journal of Critical Environmental Studies, 1996)
Since the advent of the scientific revolution, science has been purported to transcend the realm of the social. In the Western world, this is a luxury only science to enjoy. lndeed, our tolerance seems to be built into the very foundations of the scientific methodology itself: scientific methods are selected such that all values are excluded from inquiry. The thinking follows that, when used properly, scientific method generates observations that are "objective" and results that are truly "value-free'. In light of the meaning that science imparts, forging a connection between gender and science presents itself as an immediate paradox; to unearth the issues which surround thb notion inevitably entails a kind of intellectual revolution. For feminist critiques of science, the task at hand is not an easy one. [...]